2019
DOI: 10.3926/jotse.552
|View full text |Cite
|
Sign up to set email alerts
|

Web 2.0 for fostering students' social presence in online learning-based interaction

Abstract: Research in education confirmed that students engage in learning when they feel connected with others and when they play an active role in their learning process. Therefore; social presence (SP) considered as an important component of effective learning in both face-face and online learning environment. Therefore, this study intended to investigate students' perception about SP when using Web 2.0 tool for learning-based interaction and the difference in their perception based on gender and number of the semest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
0
14
0
3
Order By: Relevance
“…In this case, instructor needs to boost students' sense that they are safe with establishing the sense of trust among the learning community. Instructor need to make students aware that they may share the experience that connected to their study and to be careful about sharing sensitive personal stories (Al-dheleai & Tasir, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, instructor needs to boost students' sense that they are safe with establishing the sense of trust among the learning community. Instructor need to make students aware that they may share the experience that connected to their study and to be careful about sharing sensitive personal stories (Al-dheleai & Tasir, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Encouraging camera use probably would increase social presence by helping all parties to become better known ( Adair et al, 2021 ). Research has confirmed that students learn when they feel connected with others and when they played an active role in the learning process ( Al-Dheleai & Tasir, 2019 ). Hence, camera use might encourage learner interaction and communication by increasing learners’ social presence ( Adair et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…We speculate that this is related to the no-camera-on policy. Social presence is an important component of effective learning in an online learning environment ( Al-Dheleai & Tasir, 2019 ). Encouraging camera use probably would increase social presence by helping all parties to become better known ( Adair et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, DeSchryver et al (2009) perceive that both the interaction medium and the participants' ability are the factors that affect online SP. A recent study investigated that students perceived SP on Web 2.0, which includes SNS tools, and found that students expressed high perception of SP during learning-related discussion on Web 2.0 tool (Al-Dheleai & Tasir, 2019). Moreover, Al-Dheleai and Tasir (2019) reported a positive relationship between students' SP on SNS and perceived academic performance.…”
Section: Sp and Snsmentioning
confidence: 99%